Prosocial Managers, Employee Motivation, and the Creation of Shareholder Value - Agne Kajackaite; Dirk Sliwka (Institute of Labor Economics (IZA), 2018)
Milton Friedman has famously claimed that the responsibility of a manager who is not the owner of a firm is "to conduct the business in accordance with their [the shareholders'] desires, which generally will be to make as much money as possible." In this paper we argue that when contracts are incomplete it is not necessarily in the interest even of money maximizing shareholders to pick a manager who pursues this goal. We show in a formal model and in a series of lab experiments that choosing a manager who has a preference to spend resources for social causes can increase employee motivation. In turn, ex-post losses in shareholder value may be offset by ex-ante gains in performance through higher employee motivation.
Keywords: C91; D03; D21; J33; M52; 330; shareholder value; corporate social responsibility; incentives; motivation; experiment